Effect of the Pull and Diameter String of Badminton Racket Based on Coeffisient of Restitution Value - Arianto, Ivan Setia; Nuri, Nuri; Yulianto, Agus (Journal Of Natural Sciences And Mathematics Research, 2016)
Racket and strings is an important factor in the badminton sport. The aim of this study to analyze the pull and the diameter racket string based on restitution coefficient of shuttlecock. The variation of pull was measured used racket Vinlux Miotex Power 007. Six variation of racket string are (22, 23, 24, 25, 26, and 27) lbs. The diameter of the strings has kept constant of 0.66 mm. The other variable is the diameter variation of the strings are (0.62, 0.64, 0.66, 0.68, and 0.70) mm, respectively and the pull of the strings are kept constant of 24 lbs. Based on the result, the increasing of the pull was decreased the COR value, from 0.541 to 0.374 for 22 lbs to 27 lbs, respectively. Furthermore, the similar trend for the diameter variation with the pull variation, the COR value was decreases with the increasing of the diameter, from 0.529 to 0.447 for (0.62 to 0.70) mm. We can conclude, the increases of the pull and diameter variation was decresed COR value of shuttlecock. Â©2016 JNSMR UIN Walisongo. All rights reserved.